The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1371/journal.pone.0039262
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of Protein C Inhibitor with the Type II Transmembrane Serine Protease Enteropeptidase

Abstract: The serine protease inhibitor protein C inhibitor (PCI) is expressed in many human tissues and exhibits broad protease reactivity. PCI binds glycosaminoglycans and certain phospholipids, which modulate its inhibitory activity. Enteropeptidase (EP) is a type II transmembrane serine protease mainly found on the brush border membrane of epithelial cells in the duodenum, where it activates trypsinogen to initiate the digestion of food proteins. Some active EP is also present in duodenal fluid and has been made res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
11
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 51 publications
1
11
0
Order By: Relevance
“…The eight amino acid sequence, 164 RKKRSTSA, containing the furin cleavage site (furin cleaves the peptide bond between R-S) in the mature wild-type PrAg protein (PrAg-WT) was replaced with the sequence 164 FTFRSARL (to create PrAg-PCIS) using an overlap PCR strategy. This substrate sequence was derived from a region of protein C inhibitor (PCI, SERPINA5 ), within the reactive center loop and close to the C-terminus, and is known to be cleaved by testisin [ 65 ], as we confirmed (Figure 1A ), as well as by other serine proteases [ 66 68 ]. The mutant and wild-type PrAg cDNAs were expressed in the non-virulent B. anthracis strain BH460, and the secreted PrAg proteins purified in high yield using established protocols [ 69 ].…”
Section: Resultssupporting
confidence: 58%
“…The eight amino acid sequence, 164 RKKRSTSA, containing the furin cleavage site (furin cleaves the peptide bond between R-S) in the mature wild-type PrAg protein (PrAg-WT) was replaced with the sequence 164 FTFRSARL (to create PrAg-PCIS) using an overlap PCR strategy. This substrate sequence was derived from a region of protein C inhibitor (PCI, SERPINA5 ), within the reactive center loop and close to the C-terminus, and is known to be cleaved by testisin [ 65 ], as we confirmed (Figure 1A ), as well as by other serine proteases [ 66 68 ]. The mutant and wild-type PrAg cDNAs were expressed in the non-virulent B. anthracis strain BH460, and the secreted PrAg proteins purified in high yield using established protocols [ 69 ].…”
Section: Resultssupporting
confidence: 58%
“…Recently, it has been shown that protein C inhibitor (PCI) and, to a lesser extent, antithrombin, may regulate the function of enteropeptidase. However, PCI does not inhibit enteropeptidase in vivo 12 . In this study, we characterized the antithrombin-mediated inhibition of enteropeptidase and investigated the effects of antithrombin on tumor cell migration, invasion and angiogenesis.…”
mentioning
confidence: 93%
“…It belongs to clade A of the serpin ( ser ine p rotease in hibitor) superfamily ( 1 ) and was initially identified in human plasma as an inhibitor of the anticoagulant serine protease activated protein C (aPC) ( 2 ). Subsequently, PCI was recognized to be an inhibitor of many other serine proteases including blood coagulation factors ( 3 ), fibrinolytic enzymes ( 4 , 5 ), tissue kallikrein ( 6 ), acrosin ( 7 ), hepatocyte growth factor activator ( 8 ), and enteropeptidase ( 9 ). Like other serpins, PCI inhibits its target proteases by forming covalent enzyme-serpin complexes ( 10 ).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, glycosaminoglycans and phospholipids present on cell membranes ( 13 , 18 ) may not only mediate the permeation of PCI through membranes but may also bring PCI into close vicinity of cell membrane-associated serine proteases. To the best of our knowledge, there are only a few publications about the interaction of PCI with membrane-associated serine proteases ( 9 , 19 , 20 ). Among those reports, enteropeptidase is the only membrane-anchored serine protease whose interaction with PCI has been biochemically characterized ( 9 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation